2015
DOI: 10.3109/03630269.2015.1041037
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Spectrum of α-Thalassemia in Guizhou Province of South China

Abstract: α-Thalassemia (α-thal) is one of the most prevalent genetic diseases in the world and is especially frequent in tropical and subtropical regions, including South China. The aim of this study was to investigate the prevalence and spectrum of α-thal in Guizhou Province as this information was unknown. A total of 40 α-thal carriers were determined in 1219 newborn umbilical cord blood samples by hemoglobin (Hb) electrophoresis combined with DNA analysis, which revealed that the carrier rate of α-thal in Guizhou Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
8
2
Order By: Relevance
“…The carrier rate (8.91%) for α‐thalassemia in this study was significantly higher than the previously reported 3.28% in Guizhou 7 . These differences may be related to the sample sizes and the detection method of thalassemia gene.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The carrier rate (8.91%) for α‐thalassemia in this study was significantly higher than the previously reported 3.28% in Guizhou 7 . These differences may be related to the sample sizes and the detection method of thalassemia gene.…”
Section: Discussioncontrasting
confidence: 81%
“…Qianxinan State, one of its states, located in southwestern Guizhou Province, and adjacent to Yunnan and Guangxi, is geographically linked to the high incidence of thalassemia in this region. Previous studies on thalassemia have been limited due to small sample size, and most of the study subjects were children plus adults 6,7 . The thalassemia carrier rate in the Guizhou population has not yet been subjected to a large‐scale and more comprehensive epidemiological survey.…”
Section: Introductionmentioning
confidence: 99%
“…To compare and determine whether NGS genotyping is superior to traditional hematological tests plus Gap-PCR genotyping, we analyzed all the samples with NGS. NGS combined with Gap-PCR was used to screen thalassemia gene mutations, and the speci c experimental methods were the same as those used in our previous studies [3,8].…”
Section: Ngs Genotypingmentioning
confidence: 99%
“…Thalassemia is highly epidemic in southern provinces of China, and it has been a serious public health problem in those regions. Thus, prevention of thalassemia has become a strategic need to reduce birth defects in southern China [3]. Guizhou, as one of the high-incidence province of thalassemia, was populated by multiple ethnic groups, and genetic screening and counseling is usually not available due to economic di culties.…”
Section: Introductionmentioning
confidence: 99%
“…A-thalassemia is an inherited hemoglobin disorder prevalent in Southeast Asia, the Mediterranean region, and Southern China caused by an α-globin synthesis disorder due to deletions or mutations within the genes that encode the α-globin chains [Weatherall 2010;Huang et al 2015;Harteveld and Higgs 2010]. More than 95% of α-thalassemia cases are deletions rather than non-deletional mutations [Bergstrome and Poon 2002].…”
Section: Introductionmentioning
confidence: 99%